Cinacalcet, Fibroblast Growth Factor-23, and Cardiovascular Disease in Hemodialysis: The Evaluation of Cinacalcet HCl Therapy to Lower Cardiovascular Events (EVOLVE) Trial. Issue 1 (7th July 2015) - Moe, Sharon M.; Chertow, Glenn M.; Parfrey, Patrick S.; Kubo, Yumi; Block, Geoffrey A.; Correa-Rotter, Ricardo; Drüeke, Tilman B.; Herzog, Charles A.; London, Gerard M.; Mahaffey, Kenneth W.; Wheeler, David C.; Stolina, Maria; et al.
Abstract : Background—: Patients with kidney disease have disordered bone and mineral metabolism, including elevated serum concentrations of fibroblast growth factor-23 (FGF23). These elevated concentrations are associated with cardiovascular and all-cause mortality. The objective was to determine the effects of the calcimimetic cinacalcet (versus placebo) on reducing serum FGF23 and whether changes in FGF23 are associated with death and cardiovascular events. Methods and Results—: This was a secondary analysis of a randomized clinical trial comparing cinacalcet to placebo in addition to conventional therapy (phosphate binders/vitamin D) in patients receiving hemodialysis with secondary hyperparathyroidism (intact parathyroid hormone ≥300 pg/mL). The primary study end point was time to death or a first nonfatal cardiovascular event (myocardial infarction, hospitalization for angina, heart failure, or a peripheral vascular event). This analysis included 2985 patients (77% of randomized) with serum samples at baseline and 2602 patients (67%) with samples at both baseline and week 20. The results demonstrated that a significantly larger proportion of patients randomized to cinacalcet had ≥30% (68% versus 28%) reductions in FGF23. Among patients randomized to cinacalcet, a ≥30% reduction in FGF23 between baseline and week 20 was associated with a nominally significant reduction in the primary composite end point (relative hazard, 0.82; 95% confidence interval, 0.69–0.98), cardiovascular mortality (relative hazard, 0.66; 95% confidence interval, 0.50–0.87), sudden cardiac death (relative hazard, 0.57; 95% confidence interval, 0.37–0.86), and heart failure (relative hazard, 0.69; 95% confidence interval, 0.48–0.99). Conclusions—: Treatment with cinacalcet significantly lowers serum FGF23. Treatment-induced reductions in serum FGF23 are associated with lower rates of cardiovascular death and major cardiovascular events. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00345839. Abstract : Supplemental Digital Content is available in the text.